Promoting healthy computer use among middle school students: A pilot school-based health promotion program - Ciccarelli, Marina; Portsmouth, Linda; Harris, Courtenay; Jacobs, K. (IOS Press, 2012)
Background: Introduction of notebook computers in many schools has become integral to learning. This has increased students’ screen-based exposure and the potential risks to physical and visual health. Unhealthy computing behaviours include frequent and long durations of exposure; awkward postures due to inappropriate furniture and workstation layout, and ignoring computer-related discomfort. Objective: Describe the framework for a planned school-based health promotion program to encourage healthy computing behaviours among middle school students. Methods: This planned program uses a community-based participatory research approach. Students in Year 7 in 2011 at a co-educational middle school, their parents, and teachers have been recruited. Baseline data was collected on students’ knowledge of computer ergonomics, current notebook exposure, and attitudes towards healthy computing behaviours; and teachers’ and self-perceived competence to promote healthy notebook use among students, and what education they wanted. The health promotion program is being developed by an inter-professional team in collaboration with students, teachers and parents to embed concepts of ergonomics education in relevant school activities and school culture. End of year changes in reported and observed student computing behaviours will be used to determine the effectiveness of the program. Significance: Building a body of evidence regarding physical health benefits to students from this school-based ergonomics program can guide policy development on the healthy use of computers within children’s educational environments.